Microcystic/Reticular Schwannoma of the Frontal Lobe: An Unusual Occurrence. (27th March 2017) - Pearson, Lauren; Akture, Erinc; Wonderlick, Julien; Fuller, Gregory; Zenali, Maryam
Abstract : Schwannoma is a benign peripheral nerve sheath tumor that typically involves cranial nerves of the head and neck region. Intraparenchymal occurrence of this tumor is uncommon. Even rarer in this site is the microcystic/reticular pattern of schwannoma. This histologic variant, first described in 2008, has a predilection for visceral organs. Herein, we report the first case of microcystic/reticular schwannoma of the frontal lobe.